(untitled) (Research, Society and Development, 2022)
Pregnancy is characterized by numerous physiological changes, which can lead to a variety of symptoms and minor disorders such as: gastrointestinal, such as nausea, reflux, constipation, low back pain and headache. to relieve their discomfort, they should be accompanied by a pharmaceutical professional due to the risk of a toxic or teratogenic effect on the embryo/fetus when exposed to a certain drug, which can lead from a congenital malformation to fetal death, a fact unknown among most of pregnant women. The objective of this study was to evaluate the irrational use of medication in the gestational period, reviewing the safety of the most used drugs during pregnancy, and the importance of pharmaceutical monitoring. To this end, a study review was carried out in the Scielo (Scientific Electronic Library), Lilacs (Latin American and Caribbean Literature on Health Sciences) databases through the VHL platform (Virtual Health Library), PubMed access site from the Medline database, with studies identified in the period from 2016 to 2022. Results show the need to help raise awareness about the variables inherent to pregnancy, seeking to highlight the importance of the pharmacist in this period, as an appropriate and responsible professional to promote the use Medicines Rationale (URM).